Surgical Correction of Patellar Luxation in a Rabbit. (7th August 2013) - Riggs, J.; Langley-Hobbs, S. J.
Abstract : A two-and-a-half-year-old giant lop-eared rabbit, weighing 5.1 kg, presented with a one-month history of intermittent right hind limb lameness. The limb locked in extension during hopping. On examination, a grade-2 medial patellar luxation of the right hind was diagnosed, with associated stifle joint swelling. Radiographic findings of the right stifle comprised periarticular osteophyte formation consistent with mild degenerative joint disease and joint effusion. Surgical correction involving right trochlear wedge recession sulcoplasty and lateral imbrication was carried out to stabilise the patella in the trochlear groove. The right hind limb lameness resolved, and the patella was stable at a 6-month postoperative examination. One year postoperatively, the right patella was luxating again concurrent with bilateral stifle effusions. Euthanasia was performed twenty months after surgery due to recurrent lameness in the right hind limb.